Wujud Ungkapan Lingkungan Hidup Pesona Alam pada Surat Kabar Kompas Edisi November 2015 - Januari 2016 Sebagai Implementasi Pembelajaran Bahasa Indonesia - Astuti, Wahyu Wiji; , Drs. Agus Budi Wahyudi, M.Hum (2016)
The purpose of this study is to describe expression form of life environment, to describe lexicon sign and the implantation in learning Indonesian subject. Method of profiding data using thechiques involved and thechiques notes. Data analysis using agih. The results of data can be found a form of expression sign 4 phrase said a totaled of 11 phrases, synonyms totaled 7 expression antonyms words amounted to 7 expression, said hyponymy and hypernymy amounted to 8 expression. The phrase froms of live environment is implemented as an object of learning Indonesian subject for text material of observation results. The part implemented is lexicon sign of live environment form Kompas Keyword: phrase form,lexicon sign, implementation